β-Mannanase Supplementation as an Eco-Friendly Feed Strategy to Reduce the Environmental Impacts of Pig and Poultry Feeding Programs - Hickmann, Felipe M. W.; Andretta, Ines; Létourneau-Montminy, Marie-Pierre; Remus, Aline; Galli, Gabriela M.; Vittori, Juliano; Kipper, Marcos (Frontiers in Veterinary Science, 2021)
Little is still known about the environmental impacts of exogenous enzyme supplementation to feed pigs and broilers. Thus, this study aimed to assess the potential environmental impacts of producing feeds for pigs and broilers by simulating the effects of β-mannanase Hemicell HT supplementation through energy savings during diet formulation. Life-cycle assessment standards were applied to simulate a cradle-to-feed mill gate scope. The functional units used were the production of 1 kg of the enzyme and 1 kg of feed at a feed mill gate located in Concórdia, Santa Catarina, Brazil. Climate change, eutrophication, and acidification were the chosen environmental impact categories. Energy savings through β-mannanase supplementation were assessed by different metabolizable energy (ME) matrices (45 or 90 kcal of ME/kg of feed) during diet formulation in different grain production scenarios (Southern and/or Central-West origin). A total of 28 feeds were formulated based on the nutritional requirements and feeding programs described in the Brazilian Tables for Poultry and Swine, with no animal trials. The least-cost formulation method was used based on real price averages practiced in a local industry over 12 months. The production of 1 kg of β-mannanase was associated with the emission of 1800 g of CO2-eq, 4.53 g of PO4-eq, and 7.89 g of SO2-eq. For pig feed diets, β-mannanase supplementation mitigated both climate change and eutrophication impacts up to 8.5% and 1.4% (45 kcal of ME/kg of feed) or up to 16.2% and 2.7% (90 kcal of ME/kg of feed) compared to control diets formulated without the enzyme. For broiler feeds, these impacts were mitigated up to 5.6% and 1.1% (45 kcal of ME/kg of feed), respectively. On the other hand, the effect of using β-mannanase on the acidification impact was not consistent among feeds/species. Overall, β-mannanase supplementation reduced the amount of soybean oil in feed formulas, which is associated with high environmental impacts. Consequently, the potential impacts of climate change and eutrophication associated with producing feeds for pigs and broilers were substantially mitigated. These results suggest that β-mannanase supplementation is an eco-friendly feed strategy to reduce the environmental impacts of pig and poultry feeding programs.